Innovations in High-pressure Technologies for the Development of Clean Label Dairy Products: A Review. Issue 2 (17th February 2023) - Roobab, Ume; Inam-Ur-Raheem, Muhammad; Khan, Abdul Waheed; Arshad, Rai Naveed; Zeng, Xin-an; Aadil, Rana Muhammad
ABSTRACT: Pathogens or spoilage microorganism inactivation without affecting the organoleptic property opens a wide range of opportunities for the dairy industry, which is continuously facing challenges towards food safety. Dairy products are produced using a range of synthetic additives, preservatives, emulsifiers, stabilizers, antimicrobials, antioxidants, colors, and sweeteners. At the industrial level, these additives are used for substituting protein/fat for cost optimization, diversifying the flavor or texture, or extending the shelf life. Nowadays, consumers are more concerned with the formulation of food product. They are willing to pay more for natural products with fewer ingredients and free from synthetic chemicals as well as harsh processing. Clean label manufacturing also covers cost and functionality issues related to the product which is claimed to be healthy and nutritious. In the dairy industry, clean label production discourages the use of artificial/chemical additives and encourages the use of nonthermal pressure technologies such as high-pressure processing, high-pressure homogenization, ultra-high-pressure homogenization, and high-pressure jet processing. Traditional thermal processing is effective in preserving dairy products; however, high pressure-based technologies are a valid alternative to ensure nutritional quality. This review focuses on advanced knowledge about the impact of high-pressure-based technologies and their relationship to the development of clean label dairy products.